Răspuns :
a=[tex] \sqrt{4- 2\sqrt{3} } [/tex]
b=[tex] \sqrt{4+ 2\sqrt{3} } [/tex]
n=a*b⇔[tex] (\sqrt{4-2 \sqrt{3} } )*( \sqrt{4+ 2\sqrt{3} } )[/tex]
Observatie! Avem de-a face cu o diferenta de patrate.
=[tex] \sqrt{4^2-(2 \sqrt{3})^2 } [/tex]
=[tex] \sqrt{16- 4*3 } [/tex]
=[tex] \sqrt{16-12} [/tex]
= [tex] \sqrt{4} [/tex] = 2
[tex]\boxed{(a+b)(a-b)=a^2-b^2}[/tex] ⇄ Formula diferentelor de patrate
Mult noroc!
b=[tex] \sqrt{4+ 2\sqrt{3} } [/tex]
n=a*b⇔[tex] (\sqrt{4-2 \sqrt{3} } )*( \sqrt{4+ 2\sqrt{3} } )[/tex]
Observatie! Avem de-a face cu o diferenta de patrate.
=[tex] \sqrt{4^2-(2 \sqrt{3})^2 } [/tex]
=[tex] \sqrt{16- 4*3 } [/tex]
=[tex] \sqrt{16-12} [/tex]
= [tex] \sqrt{4} [/tex] = 2
[tex]\boxed{(a+b)(a-b)=a^2-b^2}[/tex] ⇄ Formula diferentelor de patrate
Mult noroc!